2012
DOI: 10.1111/j.1423-0410.2012.01657.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different dimethyl sulphoxide concentrations on cell recovery, viability and clonogenic potential of cryopreserved peripheral blood hematopoietic stem and progenitor cells

Abstract: Reduction in DMSO concentration from 10% to 7·5% may have favourable impact on hematopoietic recovery after autologous transplantation. The findings require confirmation in a clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 36 publications
(48 reference statements)
1
18
0
3
Order By: Relevance
“…Additionally, in randomly selected 13 patients, 1 mL of the product was cryopreserved separately and further tested in a clonogenic assay, for the presence of burst-forming unit-erythroid (BFU-E), CFU-erythroid (CFU-E); CFU-granulocyte/macrophage (CFU-GM) and CFU-erythroid, granulocyte, macrophage, megakaryocyte (CFU-GEMM), as previously described. 28 …”
Section: Leukapheresesmentioning
confidence: 99%
“…Additionally, in randomly selected 13 patients, 1 mL of the product was cryopreserved separately and further tested in a clonogenic assay, for the presence of burst-forming unit-erythroid (BFU-E), CFU-erythroid (CFU-E); CFU-granulocyte/macrophage (CFU-GM) and CFU-erythroid, granulocyte, macrophage, megakaryocyte (CFU-GEMM), as previously described. 28 …”
Section: Leukapheresesmentioning
confidence: 99%
“…A 2013 preclinical study, followed by two clinical trials, looked at three DMSO concentrations (10, 7.5, and 5%) for cryopreservation of HSCs [25-27]. Preclinical results showed a decrease in nucleated cell recovery for concentrations of DMSO below 10%, but found the highest number of colonies formed from cells frozen in 7.5% DMSO [25].…”
Section: New Cryoprotectantsmentioning
confidence: 99%
“…Differences regard many factors that have been demonstrated to affect the quality of the hematopoietic stem/progenitor cells after thawing. These are as follows: cell storage conditions before cryopreservation [23][24][25][26], cooling rate of cells (freezing curve) [7,18,26,27], temperature and speed of adding cryoprotective mixture [24][25][26] and final DMSO and cell concentration [21,[28][29][30][31][32][33][34][35][36]. In particular, in our previous studies, we demonstrated that cryopreservation with 7Á5% DMSO was associated with higher clonogenic potential and faster post-transplant engraftment compared with 10% DMSO [21,29].…”
Section: Discussionmentioning
confidence: 99%